THE IMPLEMENTATION OF DRILL EXERCISE VARIATIONS IN BASKETBALL LECTURING (CHEST PASS TECHNIQUE) AT THE STUDENTS OF PHYSICAL EDUCATION IN UNIVERSITY OF DEHASEN BENGKULU - Arifto Juniardi; Tito Parta Wibowo (Universitas Negeri Medan, 2019)
This study aimed to improve the results of basketball chest pass learning which had a low success rate. Based on the above problems, it was necessary to make improvements in the lecture process, so that the learning outcomes target reached the KKM score. The success of lecturing was when the KKM value set by the study program achieved. The type of research was classroom action research with research subject students who took part in basketball lectures and lecturers who taught basketball courses. The population in this study was the Physical Education Study Program at FKIP University of Dehasen Bengkulu, the sample was the Physical Education Study Program for Semester V Class A1. Chest pass was given at the beginning of the lecture, but students still had difficulties in demonstrating chest passes. Thus this matter was considered important to improve the learning outcomes. This research was conducted on the basis of the level of success of students in basketball lectures was still low when without variations in drill exercise. In this study there was 1 colleague as an observer who was in charge of providing assessment and all findings from observers were discussed together to find out how to solve problems in the process of improving the results of basketball chest pass learning. The results of this study indicated that through the application of variations in drill exercise there was an increase in the results of physical education students' FK basketball chest pass at the University of Bengkulu FKIP. Based on this conclusion, the application of variations in drill exercise was recommended as an additional teaching concept in Basketball lecture.